SMALL BUSINESS EMPOWERMENT STRATEGY IN MEDAN CITY, NORTH SUMATRA PROVINCE - Ti Aisyah; Mauludi, Mauludi; Muhammad Hasyem; Aiyub, Aiyub; Murhaban, Murhaban (Bajang Institute, 2024)
Community empowerment is a strategy used in community development as an effort to achieve competence and independence in social, national and state life. (Permendagri No. 7 of 2007). The government's empowerment strategy for small businesses has not been optimal. The problem is that small businesses do not have the ability to finance their businesses because they are vulnerable to capital, small businesses tend to have low ability to use technology. This research aims to find out how to empower small businesses in Medan City. The research method used is a descriptive qualitative method. Data collection techniques are observation, interviews and documentation. Data analysis techniques use data display, data reduction and verification and drawing conclusions. Based on the results of research on strategies for empowering small businesses in the city of Medan, it can be seen from the development dimension (enabling), the lack of training and development programs means that small business actors are not developing their businesses. Strengthening the potential (empowering) of capital and equipment assistance is still lacking and there is no equality in the distribution of this assistance. Furthermore, the dimension of creating independence for some small business actors still needs guidance to run their businesses independently. It is hoped that the empowerment of Small Businesses in the City of Medan can be increased to create independent Small Businesses which can have an impact on expanding employment opportunities and improving the economy of local communities